Analysis of the spatial association network of agricultural water use efficiency and its driving factors in China - Xu, Yueyan; Wang, Dan; Zhang, Youwang (Frontiers in Environmental Science, 2026)
Regional imbalance exist in agricultural water use efficiency across China. Promoting inter-provincial collaboration to improve the overall efficiency level is crucial for ensuring food security and resource equity. While existing research often focuses more on efficiency improvements within single geographical units, studies on spatial spillover effects and the dynamic evolution of networks are still limited. Therefore, this study measures agricultural water use efficiency in Chinese provinces from 2005 to 2023 based on the SE-SBM model, constructs a spatial association network and applies social network analysis (SNA) and the stochastic actor-oriented model (SAOM) to examine its structural characteristics and driving factors. The results show that: (1) The spatial association of agricultural water use efficiency presents a complex network structure. Provinces like Guangdong, Shanghai and Fujian plays important radiating and bridging roles in the network. Future policy design should place emphasis on strengthening their efficiency spillover effects. (2) As connections between provinces become closer, efficiency is gradually breaking through geographical limitations to form new spatial spillovers. Cross-regional water resource management strategies should take this emerging trend into account. (3) Both network structural effects and exogenous factors significantly drive the evolution of the spatial association network, highlighting the need for targeted policies and inter-provincial cooperation. By exploring the inter-provincial association of agricultural water use efficiency from a network perspective, this study provides critical insights for cross-regional cooperation in agricultural water resource management.